Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


See your first equation will be x+7y = -11 and second will be 3x-5y=6 
and by multiplying 3 in eqn.1 nad subtracting from 2 y=-3/2 and then x =-1/2
0 0 0
In equation 1 x/7+11/7=-y =&x+11=-7y =& x=-7y-11......3 In eq 2 x-5y/3=2 3x-5y=6 x=(6+5y)/3....4 Now from eq 3&4 -11-7y=(6+5y)/3 -33-21y=6+5y 26y=-39 y=-39/26 =-3/2 Substitute value of y in eq 4 x=(6+5×-3/2)/3. {Take -3/2 as -1.5) =(6-7.5)/3 =-1.5/3 =-1/2
0 0 0
Thanks so much
Sorry I had to correct
Got confused that it was (x-5y)/3 instead of x-5y/3
Had to correct the process
And please if the answer has been helpful mark it as best ,I need to gain a rank
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts